2016
DOI: 10.1016/j.jbi.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between videogame mechanics and executive functions through EEG analysis

Abstract: This paper addresses a different point of view of videogames, specifically serious games for health. This paper contributes to that area with a multidisciplinary perspective focus on neurosciences and computation. The experiment population has been pre-adolescents between the ages of 8 and 12 without any cognitive issues. The experiment consisted in users playing videogames as well as performing traditional psychological assessments; during these tasks the frontal brain activity was evaluated. The main goal wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 39 publications
0
43
0
1
Order By: Relevance
“…The authors expand on how these studies often fail to control for the variability that arises from differences in gameplay mechanics, suggesting that the cognitive effects of playing video games may differ even within a genre. This is supported by Mondéjar et al ( 2016 ) who found that variations in gameplay mechanics of video games within the same genre can activate different parts of the brain. The authors classified games into five key genres, notably subdividing action video games into two categories: timely action and accurate action.…”
Section: Impact Of Genrementioning
confidence: 69%
See 1 more Smart Citation
“…The authors expand on how these studies often fail to control for the variability that arises from differences in gameplay mechanics, suggesting that the cognitive effects of playing video games may differ even within a genre. This is supported by Mondéjar et al ( 2016 ) who found that variations in gameplay mechanics of video games within the same genre can activate different parts of the brain. The authors classified games into five key genres, notably subdividing action video games into two categories: timely action and accurate action.…”
Section: Impact Of Genrementioning
confidence: 69%
“…Kühn et al ( 2018 ) used an action video game, a genre that Powers et al ( 2013 ) reported had a moderate effect size (Cohen's d = 0.22–0.62) with respect to cognitive functioning. Research has shown that general cognitive activation and executive functioning are more linked to games that involved learning patterns and logical puzzles, components not found in Boson X, than those that are classified as action video games (Mondéjar et al, 2016 ). Subsequently, Boson X may not be an effective medium for the alleviation of depressive symptoms perhaps because it does not target the cognitive abilities that have been implicated in rumination (and depression).…”
Section: Impact Of Genrementioning
confidence: 99%
“…FFT, averaging different values, phase coherence, Correlation based Feature Selection, Bayesian network classifiers Mondejar et al [14] This paper explores cognitive skills and their training through the uses of serious games by using EEG to assess that relation.…”
Section: Johnny Andmentioning
confidence: 99%
“…There are several ways to achieve this goal, among them, facial recognition through active shape models [9], histograms of oriented gradients [10], voice recognition based on support vector machines [11] and ontological mechanisms to identify emotions and human behavior [12], and EEGbased cognitive activity [13]. As for general applications in health, it can be used for physical rehabilitation [14] or prevention of health issues [15], as well as applications in game-based approaches [16].…”
Section: Related Workmentioning
confidence: 99%